Study of Figurative Language Style in The Album ‘’Tanpa Aku ’’ by Panji Sakti - Dina Dwi Rahmawati; Irwan Satria; Vebbi Andra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research uses a song as a research object. In the song, there are some words known as lyrics that contain a message. Through the song lyrics, the writer conveys ideas, thoughts, and feelings. This research aims to describe the form and meaning of figurative language style. This research applied Library Research with a qualitative approach and content analysis was applied as a method. The data were collected by using literature techniques, observation, and documentation. Meanwhile, data validity techniques used in this study increase persistence and references. Based on the results of the research in song lyrics on the album “Tanpa Aku” the writer found that there were seven types of figurative language styles with twenty-five forms of figurative language styles. Moreover, the writer found twenty-five forms of figurative language meaning in seven kinds of language style.